A review of literature on mediators and moderators of workplace bullying: Agenda for future research. Issue 7 (16th July 2018) - Rai, Arpana; Agarwal, Upasna A.
Abstract : Purpose: During the past 26 years, there has been a phenomenal growth in the literature on workplace bullying. The purpose of this paper is to review and synthesize the extant empirical studies on underlying and intervening mechanisms in antecedents–bullying and bullying–outcomes relationships. Design/methodology/approach: In total, 53 studies on mediators and moderators in antecedents–bullying and bullying–outcomes relationships (2001-2016) were selected from academic databases (Google Scholar, Research Gate, Emerald Insight, Science Direct, etc.) Findings: The review suggests that while a reasonable number of studies examine the role of mediators and moderators in bullying–outcomes relationships, such efforts are meager in antecedents–bullying relationships. The paper concludes by proposing some potential variables that can explain the underlying mechanisms in the bullying phenomenon and alleviate/aggravate the antecedents–bullying–outcomes relationships. Originality/value: To the best of authors' knowledge, this is the first review on mediators and moderators of workplace bullying.